EFFECT OF DIETARY VITAMIN E SUPPLEMENTATION ON THE BLOOD PARAMETERS OF NILE TILAPIA (OREOCHROMIS NILOTICUS) - Ispir, U.; Yonar, M. E.; Oz, O. B. (Pakistian Agricultural Scientists Forum, 2011)
This study evaluated the influence of diets supplemented with 0, 80, 160, 240 mg kg(-1) (E(0), E(80), E(160), E(240)) of vitamin E on the physiological responses of Nile tilapia (Oreochromis niloticus) fed for 3 months. Weight were not affected by dietary vitamin E concentrations. An increase (p<0.05) on the red blood cells count and on the hemoglobin concentration was obtained on treatments with 80 and 160 mg vitamin E kg(-1) relativeto control. Mean corpuscular volume presented a significant increase (p<0.05) on treatment with 240 mg vitamin E kg(-1) when compared to control. Mean corpuscular hemoglobin concentration was significantly decreased (p<0.05) on treatment with 240 mg vitamin E kg(-1). The vitamin E treatments, we noticed a significant increase (p<0.05) in the number of leucocytes relative to control. Our results suggest that 80 mg vitamin E kg(-1) is probably the most suitable concentrations for Tilapia diets, although high vitamin E diets are necessary for quantitative leucocyte increases for tilapia
Keywords: Nile Tilapia; Oreochromis niloticus; vitamin E; blood parameters